Social capital and managers' use of corporate resources - Gao, Ziqi (Journal of business ethics, 2021)
This study investigates how social capital affects managers’ use of corporate resources. We find that for firms located in U.S. counties with a high level of social capital, (i) corporate cash holdings have higher marginal value, (ii) the contribution of capital expenditures to shareholder value is higher, and (iii) acquirers experience higher announcement-period abnormal stock returns. We further find that social capital decreases both over- and under-investment, and thus improves ex post corporate investment efficiency. Our evidence suggests that in communities with a high level of social capital, strong social norms and dense social networks constrain unethical corporate behavior, which induces more efficient use of corporate resources.